Employment Concentration across U.S. Counties. - Desmet, K; Fafchamps, M (2006)
This paper examines the spatial distribution of jobs across U.S. counties between 1970 and 2000, and investigates whether sectoral employment is becoming more or less concentrated. The existing literature has found deconcentration (convergence) of employment across urban areas. Cities only cover a small part of the U.S. though. Using county data, our results indicate that deconcentration is limited to the upper tail of the distribution. The overall picture is one of increasing concentration (divergence). While this seemingly contradicts the well documented deconcentration in manufacturing, we show that these aggregate employment dynamics are driven by services. Non-service sectors--such as manufacturing and farming--are indeed becoming more equally spread across space, but services are becoming increasingly concentrated.